Analysis of Teacher Competence in Elementary School Curriculum Development - Danik Mulya Sari; Novi Sopirah; Lukman Nulhakim (Graduate Program Magister Manajemen Pendidikan, 2026)
The development of elementary school curricula is a strategic process in improving the quality of education, the success of which is greatly influenced by teacher competence. Teachers not only play a role as curriculum implementers, but also as curriculum coordinators, developers, and researchers who directly deal with the needs of students and the school environment context. This study aims to examine teacher competence in elementary school curriculum development, including pedagogical, professional, social, and personality competencies, particularly in the context of implementing the Merdeka Curriculum. This study uses a qualitative approach with a library research method, through searching and analyzing books, scientific journal articles, and relevant and up-to-date education policy documents. The results of the study show that teachers' pedagogical and professional competencies are the main foundation in designing learning that is in accordance with the characteristics of elementary school students, while social and personality competencies play an important role in supporting collaboration, innovation, and teachers' readiness to face curriculum changes. However, various challenges in curriculum development were still found, such as teachers' limited understanding of the Merdeka Curriculum philosophy, administrative burdens, and gaps in access to training and supporting facilities. Therefore, systematic and continuous efforts are needed to improve teacher competencies.